Prevalence of Anxiety and Depression among Nurses during the early phase of COVID-19: A meta-analysis - Jatt, Khalil Ahmed; Erika Sivarajan Froelicher; Abel Jacobus Pienaar; Khairunnisa Aziz Dhamani (Pakistan journal of medical sciences, 2025)
Background & Objective: The COVID-19 pandemic exposed significant mental health challenges among healthcare workers, particularly nurses, who are key frontline responders and are the largest segment of the global health workforce. Given the ongoing threat of Mpox and potential new COVID-19 variants, understanding these challenges is vital. This review estimates the prevalence of anxiety and depression among nurses during the early phase of the pandemic to inform future pandemic responses. Methods: A systematic review was conducted to identify studies published from January 1st to November 9, 2020. The quality of the included studies was assessed using the JBI Critical Appraisal Checklist. This review was reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A meta-analysis was performed using a random-effects model to estimate the pooled prevalence of anxiety and depression. Findings: Twenty-seven studies, involving 39,386 nurses from ten countries, were included in the meta-analysis. The pooled prevalence of anxiety across 24 studies was 38.54% (95% CI: 33.99, 43.10) (I2 = 97.89%). The pooled prevalence of depression in 22 studies was found to be 35.52% (95% CI: 26.61, 44.43) (I2 = 99.72%). Interpretation: The pooled prevalence of anxiety and depression in nurses caring for patients with COVID-19 during the early phase of the pandemic was higher than that in other healthcare workers. With the ongoing Mpox outbreak and the potential for future pandemics, these findings necessitate timely screening and robust mental health strategies to support nurses and enhance healthcare resilience. doi: https://doi.org/10.12669/pjms.41.2.10828 How to cite this: Jatt KA, Froelicher ES, Pienaar AJ, Dhamani KA. Prevalence of Anxiety and Depression among Nurses during the early phase of COVID-19: A meta-analysis. Pak J Med Sci. 2025;41(2):622-629. doi: https://doi.org/10.12669/pjms.41.2.10828 This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/3.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.